Integrative Smoking Cessation Stage Model for Chinese Students Studying in Korea - Hyunsoo Oh, PhD, RN; Hyesun Jeong, PhD, RN; Whasook Seo, PhD, RN (Elsevier, 2013)
Purpose: The present study aimed at developing an integrative stage model of smoking cessation behavior by combining highly predictable constructs extracted from previously verified health behavior models. The fitness of the hypothetical model was also tested. Methods: The study participants were 214 Chinese students studying in Korea, presenting high smoking rates. Perceived severity, benefit, barrier, self-efficacy, and social support were measured using the modified Attitudes-Social Influences-Self Efficacy Questionnaire. Demographic and smoking-related characteristics were also evaluated. Results: Results showed that the hypothetical model provides a good fit. Significant psychosocial predictors of smoking cessation stage were perceived benefit (p = .050), barrier (p = .003), and social support (p = .003). Among demographic and smoking-related characteristics, gender (p = .030), duration of smoking (p = .010), and previous smoking cessation experience (p = .020) were found to influence smoking cessation stage. In addition, gender, age, number of cigarettes smoked, previous smoking cessation experience, smoking-related symptoms, and smoking cessation education needs were found to influence psychosocial constructs significantly. Conclusion: The significant psychosocial predictors and demographic and smoking-related characteristics defined in the present study appear to be potent and promising predictors of smoking cessation behavior stages for a cohort of Chinese students studying in Korea.